Psicólogos, filósofos e interfaces - Rabossi, Eduardo (Análisis Filosófico, 2000)
The aim of this paper is to inquire about the possibility and conditions of an interface between the Philosophy of Mind and Cognitive Psychology. After arguing that interfacing is a problem for Naturalistic- minded philosophers (not for Canonical ones), Goldman’s tripartite classification of interface tasks, is analysed and exemplified. The final sections of the paper are devoted to the controversy concerning the role irnages and irnaginistic thinking play in a standard cognitive theory. The idea is to apply Goldman’s tasks to some of the pertinent philosophical contributions. Finally, what is really at stake in the controversy is described, alternatively, as an intratheoretic discussion affecting the cognitivist program or a clash between different ways of practicing experimental psychology or an obvious sympton of a crises affecting the theoretical relevance of the notion of representation.